OPTIMALISASI PROFITABILITAS PERBANKAN MELALUI PENGELOLAAN KECUKUPAN MODAL DAN LIKUIDITAS SERTA RISIKO KREDIT - Wardani, Made Kusuma; Ningsih, Ni Luh Anik Puspa; Dewi, Made Pratiwi (KRISNA: Kumpulan Riset Akuntansi, 2021)
As an intermediary institution, Bank’s function is to receive and distribute funds and involve on other financial transactions. In facing competition in the banking industry, bank should have a stable and increase their performance. One measure of achieving bank performance is profitability. Profitability is the company's ability to generate profits. The purpose of this study is to analyze the optimization of bank profitability through managing capital adequacy and liquidity and credit risk. This study examines one of microfinance institution, which is called BPR. The population of this study are 136 BPR in Bali. With the purposive sampling method a sample consist of 39 companies. This study uses secondary data from BPR financial statements and analyze with Path Analysis. The results of the research found, (1) Capital Adequacy has a positive and significant effect on profitability, (2) Liquidity has a positive and significant effect on profitability, (3) Credit risk has a negative and significant effect on profitability, (4) Capital Adequacy has a positive and significant effect on Credit Risk, (5) Liquidity has a negative and insignificant effect on Credit Risk, (6) Credit Risk is not able to mediate capital adequacy to the value of Profitability (7) Credit Risk does not mediate liquidity towards Profitability